Variable Power Assistance Robotic Manipulation System for Upper Arm Rehabilitation - Rahman, S. M. Mizanoor (IEEE International Conference on Rehabilitation Robotics, 2025)
We present a 1DOF power assist robotic system that can be used by stroke patients for upper arm rehabilitation. An object can be tied with the power assist robotic system, and a human patient can lift the object vertically up and lower it down continuously. The power assist robotic system provides power assistance to the human in lifting and lowering the object. The amount of power assistance could be changed, which could change the haptically perceived heaviness of the object and vice versa. Therefore, the stroke patient could adjust the perceived heaviness of the object at different stages of rehabilitation progress considering the abilities of the patient to lift and lower the object with the assist system at different stages of rehabilitation. We developed a model to quantity power assistance levels and implemented a psychophysical method to compute power assistance for different perceived heaviness of the object. In an experiment, we evaluated the performance of the power assist robotic system based on a novel evaluation scheme using healthy subjects. The results showed that the subjects were able to realize the variations in the power assistance levels due to variations in the perceived heaviness of the object. The human-robot interaction (HRI) evaluation results showed satisfactory interactions between human subjects and the power assist system. The proposed device can be used by stroke patients for free motion upper arm rehabilitation, which can improve their quality of life (QoL).